Implementation effectiveness of ‘Problem solving for better health’ training in Lesotho using mixed methods and the reach, effectiveness, adoption, implementation and maintenance (RE-AIM) framework - Doris Akolbire; Lora L. Sabin; Paballo P. Lethunya; Abhinav Sharma; Howard J. Cabral; Brian W. Jack; Nancy A. Scott (BMC Medical Education)
Abstract Background Healthcare resources have been concentrated in urban areas, leaving rural regions vulnerable to poorer health outcomes. The Problem Solving for Better Health (PSBH) program was implemented to enhance healthcare systems in resource-limited regions by training personnel to maximize existing resources in problem-solving. This study evaluated the implementation effectiveness of PSBH-Nursing (PSBHN), a nationally led initiative to train nurses in PSBH in Lesotho. Methods A mixed-methods study employing a single-group pre-test post-test design was conducted, guided by the RE-AIM theory. Training occurred from November 2021 to June 2022. Nurses completed the Problem-Solving Inventory (PSI) before and 3–6 months after training to measure changes in problem-solving efficacy. Quality scores were assigned to nurses’ planned quality improvement projects; project implementation was assessed 3–6 months after training. In-depth interviews (IDIs) explored changes in knowledge, problem-solving efficacy, and skills. Statistical analyses utilized paired T-tests and logistic regressions using STATA 17; content analysis was conducted on IDIs using NVivo12. Results Of 300 nurses, 89 were trained (30%) in the first year. Mainly medium or high-quality scores were achieved for the project designed. However, among 79 participants, only 49.4% reported initiating their projects. Overall problem-solving efficacy improved 3–6 months after training, but the increase was not statistically significant. Nurses reported improved knowledge, confidence and communication skills, enhanced problem-solving approaches, and increased emotional maturity in solving problems. A one-unit increase in project quality score correlated with a 35.0% increase in the odds of project initiation. Conclusion PSBHN demonstrated improved knowledge and minimal improvement in problem-solving efficacy among nurses 3–6 months post-training. However, application of skills gained in implementing their projects was insufficient. Still, PSBHN shows promise in addressing healthcare challenges in resource-limited settings. Some participants were able to start their projects but the inconsistency in follow-through suggests a need for more research into the factors that can improve completion of implementation for better health outcomes.